The development of program in on advanced –programming language (MATLAB ), To solve the rate equations of laser and to study the properties of laser emission in the case of pulse –working of laser (Q.switch) . - Dayoub, Nazir (Latakia University Journal -Basic Sciences Series, 2018)
The work includes the development of a program in an advanced – programming language. to solve two none linear related partial differential equation that form a mathematical model that describes the dynamic status of laser ,so that we can study the properties of radiation density through this type the related program ,as well as the population inversion inside the homogeneous medium of laser . We have studied the strength f the out put power as well as the population inversion in the case of pulse –working of the solid state laser Nd:YAG and the population inversion change as a function of the diameter and length of the effective medium of laser .